The Difficulties in Learning Listening: A Correlational Study among the 3rd Semester Students of English Departement - Ardhany, Raden Roro Vivikusuma; Handini, Baiq Suprapti (Universitas Hamzanwadi, 2019)
The aim of this study were: to describe the level of learning problem and the teacher?s strategies applied in teaching and learning process. The population is 3rd semester of ust yogyakarta and the sample is about 26 students. The data analysis technique was quantitative including mean score, standard deviaton and product moment. The main results of this study were: the students learning problem in listening could becategorized as low with the mean score 77.56. the students achievement could be categorized as ?moderate? with the mean score 42.05. concerning the correlation between the two variables it was revealed that there was a significant and positive correlation between the student?s learning problem and their achievement